PELATIHAN PEMANFAATAN MULTIMEDIA INTERAKTIF DI MADRASAH IBTIDAIYAH - Razilu, Zila; Iskandar, Bobi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The rapid development of information technology has created great opportunities to support innovation in education, including at the elementary level such as Madrasah Ibtidaiyah. However, the learning practices at MIN 1 Muna are still dominated by conventional methods, which tend to make students passive. Therefore, efforts are needed to introduce more engaging and interactive learning media. This community service activity focused on training students in the use of interactive multimedia, where they were only required to follow, try, and use the media prepared by the implementing team. The method applied was a training approach combined with non-participatory observation conducted over four scheduled sessions, consisting of introduction, demonstration, guided practice, and discussion with a question-and-answer session. Observation sheets were used as instruments to measure indicators of activeness, seriousness, and positive response. The results indicated a consistent increase across all indicators, with student activeness improving from 45% in the first session to 85% in the fourth, seriousness from 55% to 88%, and positive responses from 50% to 90%. It can be concluded that interactive multimedia effectively enhances student motivation and engagement, even though they were not required to create the media themselves. This program opens opportunities for the development of thematic multimedia content to be integrated into the curriculum and replicated in other madrasahs to strengthen the quality of learning. ABSTRAKPerkembangan teknologi informasi telah memberikan peluang besar dalam mendukung inovasi pembelajaran, termasuk di tingkat pendidikan dasar seperti Madrasah Ibtidaiyah. Namun, praktik pembelajaran di MIN 1 Muna masih didominasi metode konvensional yang cenderung membuat siswa pasif, sehingga diperlukan upaya untuk menghadirkan media pembelajaran yang lebih interaktif dan menarik. Kegiatan pengabdian ini berfokus pada pelatihan pemanfaatan multimedia interaktif yang ditujukan kepada siswa agar mereka dapat mencoba dan menggunakan media yang telah disiapkan oleh tim pelaksana. Metode pelaksanaan menggunakan pendekatan pelatihan berbasis observasi non-partisipatif dengan empat kali pertemuan terjadwal yang meliputi pengenalan, demonstrasi, latihan terbimbing, serta diskusi dan tanya jawab. Instrumen pengumpulan data berupa lembar observasi yang menilai indikator keaktifan, keseriusan, dan respon siswa. Hasil pelatihan menunjukkan adanya peningkatan konsisten pada ketiga indikator tersebut, di mana keaktifan siswa meningkat dari 45% pada pertemuan pertama menjadi 85% pada pertemuan keempat, keseriusan meningkat dari 55% menjadi 88%, dan respon positif dari 50% menjadi 90%. Simpulan dari kegiatan ini adalah bahwa multimedia interaktif terbukti efektif dalam meningkatkan motivasi dan keterlibatan siswa, meskipun mereka tidak dituntut untuk membuat media sendiri. Pengabdian ini membuka peluang bagi pengembangan konten multimedia tematik yang dapat diintegrasikan dalam kurikulum serta direplikasi pada madrasah lain.